Management of Human Resources and the Productivity of Workers in the Maxx Brick Company in Tacna - Espinoza Vidaurre, Sam M. (2021)
This article theoretically and statistically analyzed the relationship between human resource management and worker productivity in the company Ladrillera Maxx in Tacna, a private Peruvian company that manufactures bricks and the like. This research used the statistical technique of Pearson's correlation coefficient to investigate the relationships of both variables in a sample of 92 workers. The research was descriptive correlational level of quantitative nature, the data collection method was a survey using an appropriate questionnaire. The results of the data analysis showed that there is a significant correlation between the six dimensions of human resource management with the productivity of workers in the organization studied. The need for organizations to incorporate human capital management as part of their development strategies, competitive advantages and process improvement is demonstrated.